Dynamic Use Diffusion Model in a Cross‐National Context: A Comparative Study of the United States, Sweden, and India1. Issue 1 (17th October 2012) - Shih, Eric; Venkatesh, Alladi; Chen, Steven; Kruse, Erik
<x xml:space="preserve">Abstract</x> This study proposes a model of dynamic use diffusion that serves as a basis for investigating post‐adoption technology‐usage behavior. Dynamic use diffusion measures the extent to which technology usage has evolved since the time of adoption. Herein, antecedents and consequences of dynamic use diffusion are investigated. A large‐scale, random sample survey was conducted in the United States, Sweden, and India on the use of Internet and computing technology. The survey results suggest that while the antecedents of dynamic use diffusion are similar across the three countries, the consequences are somewhat different for India. These differences can be attributed to the national cultural differences of India compared with the United States and Sweden with regard to power distance beliefs.